2013
DOI: 10.1152/ajprenal.00006.2013
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria induces a proinflammatory and profibrotic response in cortical collecting ducts via the 24p3 receptor

Abstract: Albuminuria is strongly associated with progressive kidney tubulo-interstitial damage and chronic kidney disease (CKD) progression. In proteinuric nephropathies, albumin reabsorption by the proximal tubule is saturated and the distal nephron is exposed to high concentrations of luminal albumin that may produce adverse effects. Since proximal tubular cells exposed to albuminuria exhibit a proinflammatory and profibrotic response, we assessed the effect of albuminuria in the collecting duct (CD). With the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 37 publications
6
52
0
1
Order By: Relevance
“…Because albumin is also reabsorbed both in the proximal and distal nephron, 8 we reasoned that it may also alter Klotho expression. As revealed by Western blot of the kidney cortex, Klotho expression was decreased in proteinuric rats ( Figure 4, A and B).…”
Section: Proteinuric Rats Display Decreased Klotho Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because albumin is also reabsorbed both in the proximal and distal nephron, 8 we reasoned that it may also alter Klotho expression. As revealed by Western blot of the kidney cortex, Klotho expression was decreased in proteinuric rats ( Figure 4, A and B).…”
Section: Proteinuric Rats Display Decreased Klotho Expressionmentioning
confidence: 99%
“…Recently, we demonstrated that albumin uptake also occurs in distal segments of the renal tubule, in part via 24p3R, a neutrophil gelatinase-associated lipocalin receptor expressed in the distal convoluted tubule and cortical and medullary collecting duct. 8 Proteinuria has been associated with renal dysfunction via a direct toxic effect on proximal tubular cells and the distal nephron. 8,9 High plasma phosphate, even in the upper normal range, is correlated with increased cardiovascular risk, independent of renal function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that excessive uptake of albumin into RPTC triggers apoptosis 30,4143 and generation of pro-fibrotic factors, such as TGF-beta 44 . To determine the order by which these processes are initiated, we incubated RPTC with fatty acid and endotoxin-free albumin (10 mg/mL) for 2, 4, 8 and 18 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent issue of American Journal of Physiology-Renal Physiology, Dizin et al (2) have presented convincing evidence that proximal tubule may not be the only culprit in proteinuria induced tubulointerstitial injury. Their data suggested that proteinuria-induced damage may be multifaceted and a more thorough examination of distal nephron may be required to elucidate the cause of proteinuria induced tubulointerstitial damage in proteinuric states.…”
mentioning
confidence: 99%